Math, asked by bhumika2932, 3 months ago

simplify (3^-1-5^-1 )^-1
answer fast

Answers

Answered by pvsnmurthy22
1

Answer:

Given

5

−7

×6

−5

3

−5

×10

−5

×125

=

3

5

×10

5

125×5

7

×6

5

=

10×10×10×10×10×3

5

125×5×5×5×5×5×5×5×6

7

=

2×2×2×2×2×3×3×3×3×3

125×25×6×6×6×6×6×6×6

=125×25×36

=5

3

×5

2

×6

2

5

5

×6

2

=3125×36

=112500

Answered by ramkrishnanj10
2

Answer:

  {({3}^{ - 1} -  {5}^{ - 1})}^{ - 1}   \\  =  {( \frac{1}{3}  -  \frac{1}{5}) }^{ - 1}  =  { (\frac{(5 - 3)}{15}) }^{ - 1}  =(  { \frac{2}{15}) }^{ - 1}  =  \frac{15}{2}

Similar questions